2020
DOI: 10.22603/ssrr.2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Evaluation around the Cervical Nerve Roots during Ultrasound-Guided Cervical Nerve Root Block

Abstract: Introduction: To carry out ultrasound-guided cervical nerve root block (CNRB) safely, we investigated the frequency of risky blood vessels around the target nerve root and within the imaginary needle pathway in the actual injecting position. Methods: 30 patients (20 men, 10 women) with cervical radiculopathy who received ultrasound-guided CNRB were included in this study. We defined a risky blood vessel as an artery existing within 4 mm from the center of the target nerve root or located in the range of 2 mm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…This study revealed that SIJP occurs much earlier than previously reported in cases of spinal deformity surgery using S2AI screws. Furthermore, it is clinically significant that SIJP, which occurs when perioperative physical therapy is important, is relieved by ultrasound-guided SIJ block, which can be performed quickly at the bedside, and patients are not exposed to radiation 20 . To date, the reason underlying this condition has not been determined, possibly because of its misdiagnosis as a type of wound pain or donor site pain that cannot be relieved 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study revealed that SIJP occurs much earlier than previously reported in cases of spinal deformity surgery using S2AI screws. Furthermore, it is clinically significant that SIJP, which occurs when perioperative physical therapy is important, is relieved by ultrasound-guided SIJ block, which can be performed quickly at the bedside, and patients are not exposed to radiation 20 . To date, the reason underlying this condition has not been determined, possibly because of its misdiagnosis as a type of wound pain or donor site pain that cannot be relieved 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The average follow-up period was 16.5 ± 3.5 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) months. The average age of the 94 patients was 72.1 (±4.9) years, and the majority (89/94) were females.…”
Section: Characteristics Of the Sijp-positive Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound can be quickly performed at the bedside, and patients are not exposed to radiation. It allows physicians to safely and accurately carry out various medical procedures [10,11] and to rapidly assess the target anatomy in operating theaters, intensive care units, emergency departments, and even in remote environments.…”
Section: Introductionmentioning
confidence: 99%
“…However, such a procedure bears the risk of accidental intravascular injection and can cause fatal complications, such as brain stem and spinal cord infarctions [ 3 ]. In contrast, ultrasound (US)-guided cervical selective nerve root block (SNRB) is a safer alternative procedure because it can be performed while identifying dangerous structures, including blood vessels and peripheral nerves around the target nerve root [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%